Impact of chronic kidney disease on long-term ischemic and bleeding outcomes in medically managed patients with acute coronary syndromes: Insights from the TRILOGY ACS Trial. Issue 6 (October 2016) - Melloni, Chiara; Cornel, Jan H; Hafley, Gail; Neely, Megan L; Clemmensen, Peter; Zamoryakhin, Dmitry; Prabhakaran, Dorairaj; White, Harvey D; Fox, Keith AA; Ohman, E Magnus; Armstrong, Paul W; Roe, Matthew T
Aims: We aimed to study the relationship of chronic kidney disease stages with long-term ischemic and bleeding outcomes in medically managed acute coronary syndrome patients and the influence of more potent antiplatelet therapies on platelet reactivity by chronic kidney disease stage. Methods and results: We estimated creatinine clearance for 8953 medically managed acute coronary syndrome patients enrolled in the Targeted Platelet Inhibition to Clarify the Optimal Strategy to Medically Manage Acute Coronary Syndromes trial. Patients were classified by chronic kidney disease stage: normal renal function/mild (creatinine clearance >60 mL/min); moderate (creatinine clearance 30–60 mL/min); severe (creatinine clearance <30 mL/min). Kaplan–Meier event rates through 30 months were evaluated for ischemic (cardiovascular death, myocardial infarction or stroke; primary end point) and bleeding (Global Use of Strategies to Open Occluded Coronary Arteries and Thrombolysis In Myocardial Infarction bleeding) outcomes by chronic kidney disease stage and treatment allocation (prasugrel vs. clopidogrel) within each stage. Adjusted hazard ratios (95% confidence intervals) for moderate and for severe chronic kidney disease vs. normal/mild chronic kidney disease were estimated. Platelet reactivity at 30 days was assessed in a subset of patients ( n = 1947). The majority of patients were in the normal/mild chronic kidney disease group (67%), followed by moderate chronic kidney disease (29%) and severe chronic kidney disease (4%). The incidence of ischemic and bleeding outcomes increased sharply across chronic kidney disease stages and no significant treatment interactions were observed. The adjusted risk of the primary end point increased across chronic kidney disease stages (moderate vs. normal/mild: hazard ratio 1.26; 95% confidence interval 1.09–1.46; severe vs. normal/mild: hazard ratio 1.60; 95% confidence interval 1.25–2.04). Platelet reactivity was lower in patients treated with prasugrel compared with clopidogrel, across all three chronic kidney disease stages. Conclusions: Among medically managed acute coronary syndrome patients, the long-term risks of ischemic and bleeding outcomes increased markedly with worse chronic kidney disease stages. Despite lower platelet reactivity of prasugrel compared with clopidogrel, no treatment interactions for ischemic and bleeding outcomes were observed.